Cu A -Based Chimeric T1 Copper Sites Allow for Independent Modulation of Reorganization Energy and Reduction Potential - Szuster, Jonathan (2020)
Attaining rational modulation of thermodynamic and kinetic redox parameters of metalloproteins is a key milestone towards the (re)design of proteins with new or improved redox functions. Here we report that implantation of ligand loops from natural T1 proteins into the scaffold of a CuA protein leads to a series of distorted T1-like sites that allow for independent modulation of reduction potentials (E°’) and electron transfer reorganization energies (). On the one hand E°’ values could be fine-tuned over 120 mV without affecting . On the other,  values could be modulated by more than a factor of two while affecting E°’ only by a few millivolts. These results are in sharp contrast to previous studies that used T1 cupredoxin folds, thus highlighting the importance of the protein scaffold in determining such parameters.